Should all excised surgical specimens be examined microscopically? A case report - Raymond, Thomas M (BioMed Central, 2010)
BACKGROUND: Microscopic examination of all surgical specimens is controversial. CASE PRESENTATION: We report two cases where examination has revealed unexpected results that have changed patient management and treatment. CONCLUSIONS: Histopathological examination of all tissue should be considered. The benefits and disadvantages of routine examination of tissue are discussed.